Adult Math Skills and Its Promotion in the Baltic States: Citizens and Employers Assessment - Vintere, Anna; Balode, Ilze (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
In order to activate the role of mathematics in the lifelong context, discuss how to improve/ disseminate mathematics competence in society as well as evaluate the role of mathematics in professional / personal development, Transnational comparative study on the mathematics educational needs was carried out in the Baltic States by the financial support of the Nordic Council of Ministers. This article analyses the inhabitants’ and employers' responses to the questions about the basic knowledge of mathematics assessment. In the study used self-assessment method, so the results are based on respondents' views.